Neuromyelitis optica spectrum disorder and active tuberculosis. Issue 1 (2nd January 2020) - Grieve, James Kerr; Day, Scott; Connell, David; O'Riordan, Jonathan
Abstract : Tuberculosis is on the rise again. It brings with it potential for neurological involvement both as a direct infection and as a parainfectious process. Accordingly we report the development of neurological problems affecting a 48-year-old patient's vision and sensation while being treated for active tuberculosis. At its nadir her vision deteriorated to nil perception of light and she had a sensory level to T10. Neuromyelitis optica spectrum disorder was diagnosed. We discuss our management strategy with neuromodulation in the context of active tuberculosis infection.